(untitled) (Cardiovascular Journal, 2020)
From last two decades, coronaviruses have led to three major outbreaks that started from 2002 with SARS-CoV, then MERS-CoV in 2012 and currently SARS-CoV-2 (COVID-19). There is limited data regarding the demographics and clinical features of SARS-CoV-2 infection in children. This information is especially important as pneumonia is the single leading cause of death in children worldwide. This Systematic Review aims to elucidate a better understanding of the epidemiologic, clinical and diagnostic findings, treatment and prevention options as well as global impact of COVID- 19 on the pediatric population with a focus on status in Bangladesh. Cardiovasc. j. 2020; 13(1): 62-74